Selection of Municipal Wastewater Reuse Technology for Agricultural Water by Using Multi Criteria Analysis (MCA): The Case of Walcheren Wastewater Treatment Plant, The Netherlands - Ni Nyoman Nepi Marleni; Am Maisarah Lindawati; Luqman Saleh; Nurkhakim Andriani; Ristie Ermawati; Nitis Aruming Firdaus (Center for Journal Management and Publication, 2020)
The water demands for agricultural purposes are increasing along with the population growth. Unfortunately, the water source is not sufficiently available nowadays. Furthermore, the quality of available water is more deteriorated due to the contamination from many sources such as households, industrial areas and other activities. Water board Scheldestromen handles 16 wastewater treatment plants located in Province of Zeeland in The Netherlands. The total production of treated effluent water from 16 wastewater treatment plants is 50 million annually. Quality of the effluent is relatively good, however, some potential risks related to the number of pathogenic microorganism and some trace metals are still there. The treated effluent is mostly discharged to river near to the treatment plant. The high amount of effluent discharge would potentially to be re-used for fulfill the demand for agricultural water. Therefore, this study aims to evaluate the feasibility of treated effluent from one of Walcheren wastewater treatment plants located in Ritthem, Province of Zeeland.This study uses the method of Multi Criteria Analysis (MCA) for looking the best way to re-use the effluent for agricultural purposes. The MCA questionnaire was developed based on the thorough literature review of effluent reuse. There are 6 criteria that need to be weighted and 6 scenario alternatives that need to be scored for the MCA questionnaire. The result show that the effluent water contained pathogenic bacteria (E.Coli) and some trace metals (Ni and Cu) more than suggested by FAO standard. Hence the most preferred technology is combination between closed conduits and UV system, with weighted score 0.78 while others had less weighted score compared to the selected one